2019
DOI: 10.3390/healthcare8010005
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Analysis of the Pollutant Emissions Impact on Human Health in China Industries Based on the Meta-Frontier DEA

Abstract: Environmental pollutant emissions have become increasingly serious, and the resulting human health problems have become the focus of social attention. In this study, 30 provinces in China were selected as the object of study, SO2, NOX (nitrogen oxide), and PM2.5 were taken as undesirable outputs, and a meta-frontier dynamic data envelopment analysis model was adopted to avoid the disadvantages of static analysis. In this paper, energy efficiency, environmental pollution efficiency, and human health efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Their findings showed that the health expenditure efficiencies present unstable trends during the period. Shi et al (42) merged the efficiencies of energy, environmental pollution, and human health and analyzed them in a two-stage framework to measure the influence of pollutant emissions in 30 provinces of China from 2013 to 2016. The data indicate that the average efficiency of health expenditure is undesirable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their findings showed that the health expenditure efficiencies present unstable trends during the period. Shi et al (42) merged the efficiencies of energy, environmental pollution, and human health and analyzed them in a two-stage framework to measure the influence of pollutant emissions in 30 provinces of China from 2013 to 2016. The data indicate that the average efficiency of health expenditure is undesirable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Air quality (AQ) and its temporal and spatial changes are determined by human activities via the release of various air pollutants (Derwent and Hjellbrekke, 2012;Fu et al, 2020;Hassan et al, 2013;Karl et al, 2019;Kukkonen et al, 2020;Lehtomäki et al, 2018;Shi et al, 2019) and modulated by meteorological conditions (Jacob and Winner, 2009;Jhun et al, 2015;Singh et al, 2013;Sofiev et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Air quality (AQ) and its temporal and spatial changes are determined by human activities via the release of various aerosols and gases (Derwent and Hjellbrekke, 2012;Fu et al, 2020;Hassan et al, 2013;Karl et al, 2019;Kukkonen et al, 2020;Lehtomäki et al, 2018;Shi et al, 2019), and modulated by meteorological conditions (Jacob and Winner, 2009;Jhun et al, 2015;Singh et al, 2013;Sofiev et al, 2020). 30…”
Section: Introduction 25mentioning
confidence: 99%